Chimeric non-antigen receptors in T cell-based cancer therapy. Issue 8 (3rd August 2021) - Guo, Jitao; Kent, Andrew; Davila, Eduardo
Abstract : Adoptively transferred T cell-based cancer therapies have shown incredible promise in treatment of various cancers. So far therapeutic strategies using T cells have focused on manipulation of the antigen-recognition machinery itself, such as through selective expression of tumor-antigen specific T cell receptors or engineered antigen-recognition chimeric antigen receptors (CARs). While several CARs have been approved for treatment of hematopoietic malignancies, this kind of therapy has been less successful in the treatment of solid tumors, in part due to lack of suitable tumor-specific targets, the immunosuppressive tumor microenvironment, and the inability of adoptively transferred cells to maintain their therapeutic potentials. It is critical for therapeutic T cells to overcome immunosuppressive environmental triggers, mediating balanced antitumor immunity without causing unwanted inflammation or autoimmunity. To address these hurdles, chimeric receptors with distinct signaling properties are being engineered to function as allies of tumor antigen-specific receptors, modulating unique aspects of T cell function without directly binding to antigen themselves. In this review, we focus on the design and function of these chimeric non-antigen receptors, which fall into three broad categories: 'inhibitory-to-stimulatory' switch receptors that bind natural ligands, enhanced stimulatory receptors that interact with natural ligands, and synthetic receptor-ligand pairs. Our intent is to offer detailed descriptions that will help readers to understand the structure and function of these receptors, as well as inspire development of additional novel synthetic receptors to improve T cell-based cancer therapy.